(untitled) (Revista Archai, 2018)
The focus of this paper concerns two domains of daily life related to the care of the body (Î·Ì” Ï„Î¿á¿¦ ÏƒÏ‰ÌÎ¼Î±Ï„Î¿Ï‚ Î¸ÎµÏÎ±Ï€ÎµÎ¯ÌÎ±) ”“ cooking and medicine ”“ both sharing a common field of intervention: food. The main goal of the inquiry is to identify points of convergence and disruption concerning those technai in a comparative study of selected passages of the Platonic dialogues and its contemporary Hippocratic treatises and gastronomic literature. The On Ancient Medicine presents the key for our analysis, by establishing that the founding principle of medicine as techne is to conceive the patient’s diet (Î·Ì” Ï„Ï‰Í‚Î½ ÎºÎ±Î¼Î½Î¿ÌÎ½Ï„Ï‰Î½ Î´Î¯ÌÎ±Î¹Ï„Î±) as a different diet from the healthy people’s diet (Î·Ì” Ï„Ï‰Í‚Î½ Ï…Ì”Î³Î¹Î±Î¹Î½Î¿ÌÎ½Ï„Ï‰Î½ Î´Î¯ÌÎ±Î¹Ï„Î±). Based on that distinction, we approach the perception of the several nuances of meaning assumed in distinct literary, sociological and theoretical contexts by both dietetic models (which we accordingly named “therapeutic table” and “healthy table”). The study proceeds through the analysis of passages from the following texts: Plato’s Gorgias, Protagoras, Alcibiades and Ion; Hippocratic On Ancient Medicine, On Affections, Aphorisms and On Regimen; Archestratus’ Hedypatheia; Culinary Books from the IV and III BC.